2007
DOI: 10.1111/j.1540-8175.2007.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Doppler Methods in the Evaluation of the Left Ventricular Systolic Function in Patients with Idiopathic Dilated Cardiomyopathy

Abstract: Doppler and tissue Doppler imaging methods correlate with traditional echocardiographic methods and can be used reliably and safely for left ventricular performance regardless of the patient's echogenity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Thus, Sm obtained by TDI has been suggested to be an alternative method in recent years in the assessment of systolic myocardial functions of various cardiac diseases 6–13 . In the studies so far, it has been demonstrated that in mixed groups, there has been an agreement between Sm derived from PWD‐TDI or color M‐mode TDI and LVEF obtained by radionuclide or echocardiographic Simpson's method 6,13–18 . However, the correlation between Sm and LVEF has not been studied adequately in healthy subjects and in patients with HF separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Sm obtained by TDI has been suggested to be an alternative method in recent years in the assessment of systolic myocardial functions of various cardiac diseases 6–13 . In the studies so far, it has been demonstrated that in mixed groups, there has been an agreement between Sm derived from PWD‐TDI or color M‐mode TDI and LVEF obtained by radionuclide or echocardiographic Simpson's method 6,13–18 . However, the correlation between Sm and LVEF has not been studied adequately in healthy subjects and in patients with HF separately.…”
Section: Discussionmentioning
confidence: 99%
“…An agreement between Sm obtained by pulsed‐wave Doppler (PWD) or by color M‐mode TDI and LVEF obtained by various other methods has already been assessed in mixed groups, and the two parameters have been determined to agree with each other 6,13–18 . However, the agreement between Sm and LVEF has not been adequately studied in healthy subjects and those with heart failure (HF) separately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pulsed TDI placed on six segments of the ventricle in PSAX, such as septal, lateral, anterior, inferior, anteroseptum, and posterior wall, also provide information about the circumferential and radial contraction of those regions . As known, systolic S wave in TDI shows the segmental contraction of the myocardium . Strain and strain rate are used as a deformation parameters of myocardium that can be evaluated with TDI or speckle tracking echocardiography (STE).…”
Section: Discussionmentioning
confidence: 99%
“…18 As known, systolic S wave in TDI shows the segmental contraction of the myocardium. 19 Strain and strain rate are used as a deformation parameters of myocardium that can be evaluated with TDI or speckle tracking echocardiography (STE).…”
Section: Discussionmentioning
confidence: 99%